Declarative Illocutionary Acts on The 2019 Election News Discourse: Politopragmatic Study - Kusmanto, Hari (Jurnal KATA, 2019)
This study is aimed to identify declarative speech acts in the 2019 Indonesia election news headlines. The data in this study are the headline phrases that were taken from online news covering (CNN Indonesia, Liputan 6, Okezone News, Detikcom, News, Vivanews, Antara News, and Metronews). The documentation method was applied as a data collection method by observing and taking notes techniques. The data were analyzed by using the intralingual and pragmatic equivalent method. The validity of the data in this study uses the theory of triangulation. The results of the study show that the form of declarative speech acts in the headline of the 2019 election include: (1) deciding as much as 38%; (2) ban 28.4; (3) cancel 26.6%; (4) approve as much as 7%. The results show that the electoral politics in Indonesia has a tendency to lead on the particular political preferences decision.